Figurações contemporâneas da cidade e do idílio : leituras cronotópicas em meia-noite e vinte, de Daniel Galera - Santos, Tamara dos (2019)
This study aims to analyze chronotopics images, Mikhail Bakhtin’s concept that associates space and time in just one analitical formal category of analyze, in Meia-noite e vinte (2016), contemporary brazilizan’s novel written by Daniel Galera. There is a discussion about two predominans chronotopics in this novel, chronotopic of city, which space and time are together in a recomposition of chronotopic of road/of meeting that remains chronotopic’s greek type, and chronotopic of idyllic, that upgrades chronotopic of idyllic estabilished in medievals. From the perception of chronotopic’s category in novel, it ispossibleto note a dinamicbetween real and agressivecity, which individuals live like in a apocalypse without satisfaction where they must to explore their financial and personal capacities high tight. The second chronotopic, the chronotopic of idyllic, it is figurate an ideal reality associated to rural life, where it is suppose a better human life.